Revolutionizing Retail: The Exquisite Architectural Marvel of Outdoor Shopping Malls - Ahmad Luthfi Kurniadi; Ahmad Gamal (Department of Architecture Universitas Muhammadiyah Jakarta, 2024)
Outdoor shopping malls have become an integral part of the modern urban landscape, offering a unique shopping experience under the open sky. This research aims to identify factors that influence the attractiveness of outdoor shopping malls. This literature review delves into the intricate design elements and strategic considerations that underpin the allure of outdoor shopping malls. Through a meticulous analysis of 400 papers published between 2014 and 2024, encompassing a total of 112,560 citations, key insights emerge regarding the impact of architectural design on consumer behavior. The research highlights the significance of factors such as exterior aesthetics, interior layout, and urban planning in shaping the appeal of shopping centers. By integrating perspectives from architecture, economics, and sociology, this study offers a holistic understanding of how outdoor malls create immersive retail experiences. Furthermore, by examining trends in research themes and collaborations among authors, this review sets the stage for future investigations into optimizing the design and functionality of outdoor shopping destinations